Cultural Factors As Predictor Of Adjustment Process And The Role Of Self-Efficacy As A Moderator Among Expatriate Academics In Malaysia - Nadarajah, Shanthi (2019)
In 2011, the former Prime Minister of Malaysia, Dato’ Sri Mohd Najib Tun Haji Abdul Razak claimed that the Ministry of Education (MOE) needs to increase the number of international students studying in Malaysia by 2025. The enrolling number of international student is coordinated with Key Performance Index (KPI) of internationalisation of Malaysian Higher Education. This situation would increase job opportunities for those who are with PhD qualifications and attract more expatriate academics into Malaysia higher education institutions as to fulfil the needs of the international students and to put Malaysia in the world map as higher education hub. In the effort of increasing the number of international students, higher education institutions in Malaysia has drawn their attention to identify on how to better accommodate and retain expatriate academics. These efforts are resulted depending on how well the expatriate academics adjusted themselves into Malaysian academia. Adjustment difficulties among expatriate academics could affect their job performance and these may affect their decision to remain at or leave the institution.